Cultural Specificity and Universality in English Phraseology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Phraseology, encompassing idioms, proverbs, and fixed expressions, serves as a mirror to both the unique cultural heritage and shared human experiences embedded in language. This article explores the dual nature of English phraseological units, examining their cultural specificity—rooted in historical, social, and environmental contexts unique to English-speaking societies—and their universality, which aligns with cross-linguistic cognitive patterns. Drawing on conceptual metaphor theory and cross-cultural comparisons, the analysis reveals how English idioms like "kick the bucket" reflect British historical practices, while metaphors such as "anger is heat" demonstrate global embodied cognition. Implications for translation, language teaching, and intercultural communication are discussed, emphasizing the need for balanced awareness of both aspects.